A formação do jovem leitor e o conto maravilhoso: leituras plurais - França, Vanessa Cordeiro (2020)
This investigative study, linked to the Programa de Pós-Graduação in Letras, from the Universidade Passo Fundo, inserted in the line of research Reading and Reader Training, consists of an analysis of the relationship between young people and reading in high school. Thus, the main objective of this research is to introduce the wonderful contemporary tale in Brazilian Literature classes for young students from the 2nd year at a public military high school and to propose its film transposition as a way of potentializing experience in the training of these readers. Thus, the following specific objectives were outlined: to present the wonderful tale as a possibility for meaningful reading to young readers; producing short films based on Marina Colasanti's wonderful contemporary tales; and, also, providing opportunities, through significant reading experience, for the possibility of altering and expanding students' reading subjectivity. To achieve these goals, literary literacy activities were proposed based on wonderful contemporary tales by writer Marina Colasanti, which were read, studied and translated into short films. The bibliographic research that supported this work sought the following definitions: reading for young readers (PETIT, 2008; LANGER, 2005), that brings new concepts to work with literature directed to young people; literary literacy (COSSON, 2016; PAULINO, 2005), which guides the teaching of literature in the classroom; the psychology of fairytales (BETTELHEIM, 2018; CORSO & CORSO, 2006); and investigation of the influence of fantastic reading in the formation of the literary reader (TODOROV, 2010). The group involved in this study brought together 58 high school students from Colégio Tiradentes da Brigada Militar in Passo Fundo/RS. Because it is conceived as an action aimed at solving a collective problem - that of encouraging young people's interest in reading during high school -, this investigation is an action research, with a qualitative and quantitative approach. Through the guidance given to the research carried out, it was sought to show not only whether the fantastic elements would cope with the rescue for literary interest, but also whether the use of other reading platforms would positively influence readers. It was concluded that the proposed literary literacy activities, in addition to leading students to realize that wonderful tales are timeless and not aimed at specific ages, also made them expand their reading subjectivity and their perennial reading behavior.